GEOLOGICAL AND GEOMORPHOLOGICAL FACTORS OF THE SMALL RIVERS MORPHODYNAMICS (ON THE EXAMPLE OF THE CHECHVA RIVER, LIMNITSA TRIBUTARIES) - BAYRAK, Galyna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Small rivers are an important element in the structure of the earth’s surface; they take an active part in the formation of its morphological outlines. They also perform an important function in the development of medium and large rivers, influence the implementation of a general nature-preserving strategy for the use of water resources in a certain region. The problem of studying the state and changes of small rivers, as well as the factors that cause changes, is multifaceted and requires thorough research. Small rivers are most dependent on geological and geomorphological factors, so it is important to study their influence on channel changes. Methods. Topographic maps of 1906, 1910, 1927, 1944, 1981, aerial photographs of 1952, 1967, 1978, and space photographs of 2005–2024 were used to study the morphodynamics of the Chechva River. Geocoding and channel digitization were performed in QGIS. A special interactive module was developed to analyze the distribution of erosion and accumulation processes along the longitudinal profile of the river in the MS Visual Studio software package. Cartographic and field studies were used to identify the characteristics of the influence of geological and geomorphological factors on the morphodynamics of the channel. Results. The morphodynamics of the Chechva River (a left tributary of the Limnytsia) was studied based on the analysis of materials from different periods. It was manifested by transverse and longitudinal displacements of the riverbed both in the mountainous part and in the foothills. Transverse shifts of the channel, changes in the tops of meanders, and changes in the number of branches took place in the mountainous part. The spectrum of changes was wider in the foothills: the migration of the channel with a change in its straight form to winding and meandering and from meandering to straight, reversal of the convexity by 180°, changes in the width and length of the meandering zone, the dynamics of morphological types and meanders parameters. The geological factors that caused the channel changes are: the lithological composition of the rocks, in particular, the presence of flysch deposits in the mountain and loose material in the foothill’s parts of the Chechva valley, the granulometric composition of the rocks, their layered texture, significant fissures and a large number of outcrops on the banks. Geomorphological factors are essential: the morphometry of the basin with large height differences and dense and deep dismemberment, extensive forms of the transverse valley profile, changes in the slope and river fall, floodplain and channel parameters. Conclusions. Geological and geomorphological factors have both a motivating and a limiting influence on the morphodynamics of small river channels.